2021
DOI: 10.26434/chemrxiv.13003490.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring Theoretical Descriptors of Water Oxidation: Free Energy Differences Between Intermediates Using Time-Resolved Optical Spectroscopy

Abstract: <p>Theoretical descriptions differentiate catalytic activity of material surfaces for the water oxidation reaction by the stability of the reactive oxygen (O*) intermediate. The underlying conjecture is that there are several meta-stable steps of the reaction, each connected by free energy differences critically dependent on O*. Recently <i>in-situ, </i>time-resolved spectroscopy of the (<i>photo<br> </i>)-electrochemical water oxidation reaction identified the vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…2A, phonon removed) which we have studied in a previous publication. 36 In the next three sections, we will extract the frequency (3.1), amplitude (3.2), and phase (3.3) of these oscillations and use them to link the CAWs in CC to interfacial strain generated by hole-trapping to create Ti-OH * . The OC condition will be used as a foil, in which the CAWs derive instead from high photocarrier populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2A, phonon removed) which we have studied in a previous publication. 36 In the next three sections, we will extract the frequency (3.1), amplitude (3.2), and phase (3.3) of these oscillations and use them to link the CAWs in CC to interfacial strain generated by hole-trapping to create Ti-OH * . The OC condition will be used as a foil, in which the CAWs derive instead from high photocarrier populations.…”
Section: Resultsmentioning
confidence: 99%
“…1 represent the growth of an emissive signal associated with hole trapping and the decay exponential is associated with the decay of the valance band hole population (described below). 8,9,12,36,39 For hole trapping, we found that the average fast growth timescale was 1.2 ± 0.3 ps (fig. S6).…”
Section: Caws Frequencymentioning
confidence: 89%
See 2 more Smart Citations
“…Measurements for the phonon amplitude correlation were performed with a similar in-situ sample cell (3 mm CaF2 with 1 cm between the sample and window) and TR setup used previously. 36 For the TR setup, the pump and probe beams were derived from a regeneratively amplified Ti:sapphire laser system (Coherent Legend; Coherent, Inc., Santa Clara, CA) producing pulses with a center wavelength of 800 nm and ~200 fs temporal width (fig. S4A) at a 1 kHz repetition rate.…”
Section: Methodsmentioning
confidence: 99%